Stroke services in the Middle East and adjacent region: A survey of 34 hospital-based stroke services - Al Hashmi, Amal. M.; Shuaib, Ashfaq; Imam, Yahia; Amr, Dareen; Humaidan, Hani; Al Nidawi, Firas; Sarhan, Ahmed; Mustafa, Wessam; Khalefa, Wael; Ramadan, Ismail; Usman, Fritz Sumantri; Hokmabadi, Elyar Sadeghi; et al. (Frontiers in Neurology, 2022)
Background Acute stroke care is complex and requires multidisciplinary networking. There are insufficient data on stroke care in the Middle East and adjacent regions in Asia and Africa. Objective Evaluate the state of readiness of stroke programs in the Middle East North Africa and surrounding regions (MENA+) to treat acute stroke. Method Online questionnaire survey on the evaluation of stroke care across hospitals of MENA+ region between April 2021 and January 2022. Results The survey was completed by 34/50 (68%) hospitals. The median population serviced by participating hospitals was 2 million. The median admission of patients with stroke/year was 600 (250–1,100). The median length of stay at the stroke units was 5 days. 34/34 (100%) of these hospitals have 24/7 CT head available. 17/34 (50%) have emergency guidelines for prehospital acute stroke care. Mechanical thrombectomy with/without IVT was available in 24/34 (70.6%). 51% was the median (IQR; 15–75%) of patients treated with IVT within 60 min from arrival. Thirty-five minutes were the median time to reverse warfarin-associated ICH. Conclusion This is the first large study on the availability of resources for the management of acute stroke in the MENA+ region. We noted the disparity in stroke care between high-income and low-income countries. Concerted efforts are required to improve stroke care in low-income countries. Accreditation of stroke programs in the region will be helpful.